2013
DOI: 10.1016/j.anucene.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Review of the natC(n, γ) cross section and criticality calculations of the graphite moderated reactor BR1

Abstract: A review of the experimental data for nat C(n,y) and 12 C(n,y) was made to identify the origin of the nat C capture cross sections included in evaluated data libraries and to clarify differences observed in neutronic calculations for graphite moderated reactors using different libraries. The performance of the JEFF-3.1.2 and ENDF/B-VII.l libraries was verified by comparing results of criticality calculations with experimental results obtained for the BR1 reactor. This reactor is an air-cooled reactor with grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…In contrast to the presented results, calculations (Díez et al 2013) for the BR-1 reactor show a 28 much more notable effect of (n,g) on the keff. The BR-1 reactor located at the Belgian Nuclear 29…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast to the presented results, calculations (Díez et al 2013) for the BR-1 reactor show a 28 much more notable effect of (n,g) on the keff. The BR-1 reactor located at the Belgian Nuclear 29…”
contrasting
confidence: 53%
“…The presented results of the HTTR calculation show also a trend of underestimation, 7 however higher, of JENDL-4 results with regard to ENDF/B-VII.0 or JEFF-3.1. The reason is 8 a more notable effect of (n,g) on the keff as reported in (Díez et al 2013 reported experiments with comparable fuel enrichment. 12…”
mentioning
confidence: 62%
See 1 more Smart Citation